Efektivitas Pembelajaran Matematika Materi Luas Segiempat dengan Media Pembelajaran Manipulatif - Fadilah, Siti Umi; Khabibah, Siti; Sa’adah, Nihayatus (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2024)
This research referred to manipulative learning media which can be used to visualize abstract material. This research aimed to describe the effectiveness of learning mathematics regarding rectangular area using manipulative learning media. This research was quantitative descriptive research. The population in this study was 120 students of grade VII MTs Salafiyah Syafi'iyah Seblak Jombang while the sample was 21 students of grade VII D. The sample was selected using a purposive sampling technique with the consideration that grade VII D had the lowest average score in mathematics compared to other classes. Data were collected using test instrument to obtain student achievement data. The data were then analyzed descriptively and compared with the specified effectiveness criteria, that learning is said to be effective if the percentage of classical completeness exceeded 75%. The result of the research shows that the percentage of classical completeness is 85.7%, so it can be concluded that mathematics learning about the area of quadrilaterals is effective with manipulative learning media.